An efficient approach to synthesizing 2, 5-bis(N-methyl-aminomethyl)furan from 5-hydroxymethylfurfural via 2, 5-bis(N-methyl-iminomethyl)furan using a two-step reaction in one pot. Issue 15 (15th July 2021) - Zhang, Jie; Jia, Wenlong; Sun, Yong; Yang, Shuliang; Tang, Xing; Zeng, Xianhai; Lin, Lu
Abstract : A renewable synthesis pathway of 2, 5-bis( N -methyl-aminomethyl)furan from HMF using a two-step reaction in one pot. Abstract : In this study, an amination–oxidation–amination–reduction (AOAR) strategy was proposed for the synthesis of 2, 5-bis( N -methyl-aminomethyl)furan (BMAF) from HMF via the intermediate 2, 5-bis( N -methyl-iminomethyl)furan (BMIF). Firstly, an efficient synthesis of BMIF from HMF using a one-pot amination–oxidation–amination reaction was developed over α-MnO2 under an air atmosphere. A BMIF yield of 98.3% was obtained under mild reaction conditions. The conversion of HMF to BMIF underwent the fast amination of HMF to 5-(methyl-iminomethyl)furfuryl alcohol (MIFA), the subsequent rate-limiting oxidation of MIFA to 5-(methyl-iminomethyl)furfural (MIFF) and the final fast amination of MIFF to BMIF. The quick amination of MIFF to BMIF drove the oxidation reaction equilibrium toward MIFF from MIFA, which ensured the highly efficient conversion of HMF to BMIF. The investigation of the catalytic mechanism showed better lattice oxygen donating ability and oxygen coordination capacity, which made α-MnO2 retain the structural stability in the reaction. The higher ratio and better mobility of the lattice oxygen endowed α-MnO2 with excellent catalytic performance in the oxidation of MIFA to MIFF by the redox cycling of Mn 4+ /Mn 3+, facilitating the conversion of HMF to BMIF. Eventually, a BMAF yield of 96.1% was achieved by the reduction of BMIF with Ru/C after the AOA reaction, realizing the synthesis of BMAF from HMF using a two-step reaction in one pot.